PERILAKU VIRTUAL REMAJA: STRATEGI COPING, HARGA DIRI, DAN PENGUNGKAPAN DIRI DALAM JEJARING SOSIAL ONLINE - Mafazi, Naufal; Nuqul, Fathul Lubabin (Faculty of Psychology, Diponegoro University, 2017)
Teenager’s activities in the online social networks, influenced by the nature of teenager’s characteristic who tends to look for a good impression from others. This study examined the effects of coping strategies and self-esteem on the teenagers’ self-disclosure on online social networking. In total, 185 adolescents participated the study; they were identified using the purposive sampling. The sample characteristics were having a social media account and an active user of social media. The Revised Self-Disclosure Scale, the Self-Esteem Scale, and the Ways of Coping Checklist were used to collect data. The results of regression analysis showed that there is a positive and significant correlation of coping strategies and self-esteem on adolescents’ disclosure in online social networking.